Intraoperative Neurophysiologic Monitoring Correlates with Neurologic Outcome After Endovascular and Surgical Treatment of a Cervical Arteriovenous Malformation - Sánchez Roldán, M. Angeles; Tellez, Maria J.; Mora, Francisco; Ghatan, Saadi; Roonprapunt, Chanland; Ulkatan, Sedat (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The treatment of spinal intramedullary arteriovenous malformations (AVMs) presents the risk of spinal cord ischemia because of the vascular nidus and their feeding arteries involving and supplying the spinal cord parenchyma. The multimodal approach includes endovascular embolization and microsurgical excision, both benefiting from intraoperative neurophysiologic monitoring. We present a case study of a patient who underwent several staged embolizations and open surgery for microsurgical excision.Patient A 32-year-old man who presented with a recurrent glomus-type intramedullary AVM in the cervical spinal cord, located at the C5–C6 segment, with progressive neurologic deterioration.Methods Somatosensory evoked potentials (SEPs) and transcranial motor evoked potentials (MEPs) were performed during three embolizations, a provocative test, and surgery, in addition to D-wave during microsurgical excision.Results Abolished hand MEP and drop in SEP during a provocative test guided the surgeon to embolize from a safer vessel with no acute neurologic deficit after three embolizations. Before surgery, an angiography showed the left posterior spinal artery supplying the AVM. After resecting the vascular nidus from the spinal parenchyma, left-hand MEP decreased in amplitude and later abolished, and SEP decreased. Interestingly, no D-wave or distal MEPs were affected. Weakness in the left hand immediately and 2 weeks postoperatively advocates for metameric spinal cord ischemia with preservation of long spinal cord pathways.Conclusions Intraoperative neurophysiologic monitoring correlates with neurologic outcome after endovascular and surgical treatment of a cervical AVM. Intraoperative monitoring provides continuous functional information of long and metameric spinal cord pathways, which is critical when deciding on the vessel to be embolized and during microsurgical excision where the surgeon is in less control of the AVM hemodynamic flow.
Keywords: spinal arteriovenous malformations; intraoperative neurophysiologic monitoring; endovascular embolization; surgery; outcome